Upaya Pengusaha Muda Meraih Kesuksesan Berwirausaha Cigor di Tasikmalaya Melalui Media Sosial - Sipa Mutmainah; Tendi Setiadi; Risbon Sianturi (Institut Nalanda, 2024)
This study discusses the marketing strategy of the culinary business Cigor Mang Al, founded by Ali Wardana in Tasikmalaya. The business utilizes social media platforms such as Instagram and TikTok to expand its market reach and increase sales. With a limited initial capital, Ali successfully grew daily sales from 30 pieces to 250-300 pieces through creative marketing strategies on social media. This study uses a qualitative descriptive method, collecting data through interviews and observations. The results show that social media usage not only helps expand the market but also builds brand awareness and customer loyalty. Additionally, product innovation in the form of frozen food has enabled expansion to other cities like Bandung and Yogyakarta. In conclusion, the success of Cigor Mang Al demonstrates the importance of innovation, consistency in quality, and effective social media utilization in supporting the growth of culinary businesses in the digital era.